EFFECT OF TEMPE DIETERY TO CHOLESTEROL EXCRETION AND SHORT CHAIN FATTY ACID ON RATS DIGESTA CAECUM - Yulius Kiswanto (Universitas Slamet Riyadi Surakarta, 2017)
Tempe is a traditional fermented food usually made from soybeans by Rhizopus sp. Recents publicationsmentioned that the major component was dietary fiber. One which has the capacity to lowering blood cholesterollevel. The purpose of this study was to examine the effect of tempe diet on the lipid profile and cholesterolexcretion in rats. 45 male Sprague Dawley rats were used and divided into 3 groups of 15. Each group were fedan isocaloric and isoprotein diet contained different proportion of tempe (0%, 10%,20%,30% and 40%) for 4weeks. This experiment used completely randomized design.The result showed that tempe diet significantly reduced total cholesterol (12%), LDL-cholesterol (50%) andtriglyceride (50,36%) and increased HDL resulted in the higher cholesterol faeces excretion with were maximumvalue 11,9 mg/g (40% tempe) compared 5,4 mg/g (standar diet).Keywords: Tempe, diet, lipid profile, cholesterol excretion.